Resilient Software Architecture Platform for the Individual Care Plan - Mendes, David (2021)
The individual care plan (ICP) is a metamorphic being. The only steady reality that it maintains is its final objective, stated and explained in the previous chapter where the ICP is thoroughly introduced and debated. It is a fantastic beast, better described as a system of systems that is severely polymorphic due to its coverage both in level of care as well as sources of data to handle. Patient monitoring generates large volumes of data. There is the evident need of an advanced approach that can deal with these huge amounts of healthcare data extracted from various sources such as the wearable sensors, medical, and nursing records that are currently called big data. The purpose of this chapter is to introduce and discuss the software platform that is adequate to develop and deploy the system paying attention to the needs of high-availability, sensitive information security; service-level agreements for multiple healthcare interoperability; law and ruling conformance; as well as other technical and ethical aspects.